Harmonization of Next-Generation Sequencing Procedure in Italian Laboratories: A Multi-Institutional Evaluation of the SiRe® Panel - Malapelle, Umberto; Pepe, Francesco; Pisapia, Pasquale; Sgariglia, Roberta; Nacchio, Mariantonia; De Luca, Caterina; Lacalamita, Rosanna; Tommasi, Stefania; Pinto, Rosamaria; Palomba, Grazia; Palmieri, Giuseppe; Vacirca, Davide; et al. (Frontiers in Oncology, 2020)
Background: Next-generation sequencing (NGS) needs to be validated and standardized to ensure that cancer patients are reliably selected for target treatments. In Italy, NGS is performed in several institutions and harmonization of wet and dry procedures is needed. To this end, a consortium of five different laboratories, covering the most part of the Italian peninsula, was constituted. A narrow gene panel (SiRe®) covering 568 clinically relevant mutations in six different genes (EGFR, KRAS, NRAS, BRAF, cKIT, and PDGFRα) with a predictive role for therapy selection in non-small cell lung cancer (NSCLC), gastrointestinal stromal tumor, colorectal carcinoma (CRC), and melanoma was evaluated in each participating laboratory. Methods: To assess the NGS inter-laboratory concordance, the SiRe® panel, with a related kit and protocol for library preparation, was used in each center to analyze a common set of 20 NSCLC and CRC routine samples. Concordance rate, in terms of mutation detected and relative allelic frequencies, was assessed. Then, each institution prospectively analyzed an additional set of 40 routine samples (for a total of 160 specimens) to assess the reproducibility of the NGS run parameters in each institution. Results: An inter-laboratory agreement of 100% was reached in analyzing the data obtained from the 20 common sample sets; the concordance rate of allelic frequencies distribution was 0.989. The prospective analysis of the run metric parameters obtained by each center locally showed that the analytical performance of the SiRe® panel in the different institutions was highly reproducible. Conclusions: The SiRe® panel represents a robust diagnostic tool to harmonize the NGS procedure in different Italian laboratories.